Qualitative and semi-quantitative assessment of anthocyanins in Tibetan hulless barley from different geographical locations by UPLC-QTOF-MS and their antioxidant capacities - Zhang Tangwei (De Gruyter, 2021)
Tibetan hulless barley (“qingke” in Chinese) is a valuable food in Tibet. Purple qingke (PQK) and black qingke (BQK), two special pigmented types of hulless barley, have traditionally been widely cultivated and consumed in Tibet for thousands of years. The composition and contents of anthocyanins of two cultivars are unknown. This study aimed to explore the composition and contents of anthocyanins of two cultivars and their antioxidant capacities. Six anthocyanins were identified by ultra-performance liquid chromatography-quadrupole-time of flight mass spectrometry from barley, most of the anthocyanins were acylated by malonyl group. The total anthocyanin contents ranged from 141 to 2,304 μg/g in PQK and from 248.7 to 2902.9 μg/g in BQK. Furthermore, qingke has strong antioxidant activity against DPPH, ABTS˙+, and FRAP. Qingke may be useful for treating or preventing diseases caused by the overproduction of radicals.